2019
DOI: 10.1088/1361-6463/ab4762
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped nanodiamond films grown just by heating solid precursor thin layers for field emission application

Abstract: Nanodiamond films with nanoscale grain sizes are highly desired for versatile applications, such as sensors and field emitters, due to their special physical and chemical properties. In this paper, a simple, safe, green and cost-effective approach for growing intrinsic and nitrogen (N)-doped nanodiamond films just by heating the solid thin layers of glucose and/ or urea on nickel-coated stainless steel in a resistance-heating furnace is reported. The N doping concentration of 0 to 2.63 at.% can be adjusted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The fabrication of nanodiamonds by PTFE laser processing with higher pulse widths is plausible; however, the yield is small with less control and material degradation, due to the limited undercooling achieved and prolonged exposure to high temperatures [8]. These costeffective methods have been employed to produce high quality graphene and nanodiamond composites for field emission applications [9,10]. The susceptibility towards sublimation [2] also presents a considerable bottleneck in carbon thermal processing.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of nanodiamonds by PTFE laser processing with higher pulse widths is plausible; however, the yield is small with less control and material degradation, due to the limited undercooling achieved and prolonged exposure to high temperatures [8]. These costeffective methods have been employed to produce high quality graphene and nanodiamond composites for field emission applications [9,10]. The susceptibility towards sublimation [2] also presents a considerable bottleneck in carbon thermal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Guo X. et al also proved the role of N doping for improving the properties. The turn-on E and the maximum J of the synthesized ND film with ~1.95 at.% N were, respectively, reduced to ~3.6 V/µm at 10 μA/cm 2 , and raise up to 1 mA/cm 2 at 6 V/µm, and the excellent long-term emission stability can be achieved for the optimal N-doped ND film [ 15 ]. Therefore, it can be concluded that the introduction of N not just induces a n-type conductivity, but aggravates the formation of sp 2 phase carbon, and thus enhances the field emission properties of ND film.…”
Section: Field Emission Properties Of Nd Filmmentioning
confidence: 99%
“…During the last decades, many efforts, such as the N/B element doping [ 15 , 16 , 17 ], the surface morphology [ 18 , 19 ], the micropatterned structures [ 20 , 21 ], and the introduction of the high content sp 2 hybridized carbon [ 22 , 23 ], were conducted to obtain a low surface potential barrier and a low work function of the ND films, then substantially improves the field emission properties. For example, Hao T. et al reported that the ND cones synthesized by the gray-scale patterns with a focused-ion-beam (FIB) system could obtain a high emission current up to 54 μA at an applied voltage of 10 V [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its intrinsic form, diamond exhibits very high resistivity, rendering it unusable for many electrochemical applications. Traditionally, this has been commonly addressed through doping with different elements such as boron, nitrogen, phosphorous, sulfur, and arsenic. So far, boron-doped diamond is the most extensively used diamond in electrochemistry due to its high conductivity. The processes of chemical vapor deposition synthesis and boron doping ( in situ and ex situ ) are mainly utilized for the fabrication of thin films.…”
Section: Introductionmentioning
confidence: 99%